Effects of Multiple Combination Weightage using MOPSO for Motion Control Gantry Crane System - Jaafar, Hazriq Izzuan; Mohamed, Zaharuddin; Jamian, Jasrul Jamani; Mohd Aras, Mohd Shahrieel; Anuar, Mohamed Kassim; Sulaima, Mohamad Fani (2014)
This paper presents the implementation of Multi Objective Particle Swarm Optimization in controlling motion control of Gantry Crane System. Three objective functions are considered to be optimized, named (i) steady state error, (ii) overshoot, and (iii) settling time. Six cases with different setting of weight summation are analyzed in order to obtain five parameters (PID and PD) controller. A combination of PID and PD controller is observed and utilized for controlling trolley movement to desired position and reduced the payload oscillation concurrently. Various cases of weight summation values will affect to the controller parameters and system responses. The performances of the system is conducted and presented within Matlab environment.